128. Characteristics and Outcomes of Pregnant Women Hospitalized with Influenza in the United States, Flusurv-net, 2010–2019. (31st December 2020) - Holstein, Rachel; Dawood, Fatima S; Kirley, Pam Daily; Herlihy, Rachel; Yousey-Hindes, Kim; Fawcett, Emily; Monroe, Maya; Kim, Sue; Lynfield, Ruth; McMullen, Chelsea L; Muse, Alison; Billing, Laurie M; et al.
Abstract: Background: Pregnant women are at high-risk for influenza-associated hospitalization. We used data from the U.S. Influenza Hospitalization Surveillance Network (FluSurv-NET) to characterize pregnant women hospitalized with influenza. Methods: We included pregnant women (15–44 years) residing within a FluSurv-NET catchment area and hospitalized with laboratory-confirmed influenza between October 1 and April 30, during the 2010–19 influenza seasons. Clinical data were obtained on cases through medical chart abstraction. We examined trends in vaccination coverage and antiviral treatment using the Cochran-Armitage test for trend and characterized maternal interventions and maternal and fetal outcomes during hospitalization. Results: Of 9, 652 women aged 15–44 years hospitalized with influenza, 2, 697 (28%) were pregnant. Median maternal age was 28 years and median gestational age was 32 weeks; 36% were non-Hispanic white, 29% non-Hispanic black, and 20% Hispanic. Underlying conditions were present in 35% (n=931), with asthma (n=613; 22.7%) and chronic metabolic disease (n=204; 7.6%) as the most common; 12% (n=299) were current smokers. Vaccination coverage and antiviral receipt varied by season and age [Figures 1 and 2]. Overall, 31% (n=846) were vaccinated and 89% (n=2, 408) received antivirals. Five percent (n=132) had intensive care unit admission, 2% (n=52) required mechanical ventilation, 6% (n=165) developed pneumonia and 0.3% (n=9) died; median length of hospital stay was 2 days (IQR 1–3). The most common symptoms at admission included cough (68%) and fever (66%) [Figure 3]. At discharge, most women (70%; n=1865) were still pregnant while 28% (n=758) were no longer pregnant and 2% (n=44) had unknown pregnancy status. Among women who were no longer pregnant at discharge, 96% (n=726) had pregnancies resulting in live births, 3% (n=25) had pregnancies resulting in loss of the fetus or neonate, and 1.0% (n=7) had unknown birth outcome. Figure 1. Vaccination coverage among pregnant women hospitalized with laboratory-confirmed influenza by season and by age group, FluSurv-NET 2010–2019 Figure 2. Antiviral treatment among pregnant women hospitalized with laboratory-confirmed influenza by season and by age group, FluSurv-NET 2010–2019 Figure 3. Symptoms at admission among pregnant women hospitalized with laboratory-confirmed influenza by age group, FluSurv-NET 2010–2019 Conclusion: Over 9 influenza seasons, nearly one-third of women aged 15–44 years and hospitalized with influenza were pregnant. Severe maternal and fetal outcomes were rare. While most women received antivirals, fewer than one-third received current season influenza vaccine. Disclosures: Sue Kim, MPH, Council of State and Territorial Epidemiologists (CSTE) (Grant/Research Support) Melissa Sutton, MD, MPH, CDC funding (Emerging Infections Program) (Grant/Research Support)